People Welcomed This Innovation with Two Hands: A Qualitative Report of an mHealth Intervention for Community Case Management in Malawi - Nicole Ide (Ubiquity Press, 2019)
Introduction: Community Case Management (CCM) aims to improve health outcomes among children under five with malaria, diarrhea, and pneumonia, but its effectiveness in Malawi is limited by inconsistent standards of delivery characteristic of paper-based interventions. This may lead to negative impacts on child health outcomes and inefficient use of health system resources. This study evaluated the acceptability and impact of the Supporting LIFE Community Case Management App (SL eCCM App) by Health Surveillance Assistants (HSAs) and caregivers in two districts of Northern Malawi. Methods: Data were collected through semi-structured interviews with HSAs and caregivers as part of a nested study within a larger trial. We used deductive and inductive approaches during data analysis. Relevant constructs were identified from the Consolidated Framework for Implementation Research and combined with emerging concepts from the data. The Framework Method was used to chart and explore data, leading to the development of themes. Results: Seventeen HSAs and 28 caregivers were interviewed. Participants were generally enthusiastic about the SL eCCM App. Nearly all HSAs expressed a preference for the App over routine paper-based CCM. Most HSAs claimed the App was more reliable and less error prone, facilitated more accurate diagnoses and treatment recommendations, and enhanced professional confidence and respect in the community. Some HSAs believed additional features would improve usability of the App, others identified mobile network or electricity shortages as barriers. Not all caregivers understood the purpose of the App, but most welcomed it as a health and technological advancement. Conclusion: The SL eCCM App is acceptable to both HSAs and caregivers, and in most cases, preferred, as it was believed to foster improvements in CCM delivery. Our findings suggest that mobile health interventions for CCM, such as the SL eCCM App, may have potential to improve the effectiveness and efficiency of care to children under five.